Valuable elements in sludge from eight municipal wastewater treatment plants in relation to their recovery potential - Dobril Valchev; Irina Ribarova; Boyan Borisov; Viden Radovanov; Valentina Lyubomirova; Irina Kostova; Galina Dimova; Orhideya Karpuzova; Svetlana Lazarova (Environmental Sciences Europe, 2024)
Abstract Background The management of sludge from municipal wastewater treatment plants (WWTPs) is a global issue, but also an opportunity for circular reuse. Recent data show that sludge reuse in agriculture has the highest share of all utilization routes in the EU. Council Directive 86/278/EEC on the spreading of sludge in agriculture, adopted more than 35 years ago, is still relevant, notwithstanding the discussion on the need to update it. Extracting critical, strategic, and precious metals and metalloids from sludge is an alternative for sludge reuse, which offers several benefits, such as avoiding the high environmental and health risks associated with using sludge directly in agriculture. Additionally, it allows for the recovery of metals, including those listed as Critical Raw Materials by the European Commission. To implement this alternative, it is necessary to first assess the metal content in the sludge and then develop economically and technically viable technologies. In this study, the content of chemical elements in the sludge of eight full-scale WWTPs in Bulgaria is analysed with focus on: (1) assessing the suitability for agricultural application by evaluating the content of macro- and micronutrients and hazardous metals; (2) assessing the possibility of using the sludge as a source of critical and precious metals. Results For the main nutrients, the following contents as a percentage of the sludge dry weight (DW) were recorded—2.06% to 6% for N, 1.52% to 2.67% for P and 0.47% to 0.81% for K, which are in line with case studies of successful sludge application in agriculture. Only sludge samples from two WWTPs exceeded the permitted limit for hazardous metals and metalloids. On the other hand, of the 21 metal and metalloid constituents listed in the EU Critical and Strategic Material (CRM) list, at least one of the examined samples has a content above 10 mg/kg for 15 elements. The average contents in mg/kgDW of Au (1.1), Al (19,272.9), Mg (6677.6), Ti (1730.9), Ga (20.9) and As (16.6) measured in the investigated WWTPs are among the highest or second highest reported in other countries. Conclusions The results of the study show prospects for optimising and improving the reuse of sewage sludge in Bulgaria. Sewage sludge from most WWTPs has potential for agricultural application due to its high nutrient content. Large amounts of accumulated critical and strategic metals, gold and silver are trapped in Bulgarian sewage sludge, indicating that sewage sludge could be considered an alternative source with high potential for these valuable elements.